A marginal Jew. Rethinking the historical Jesus Vol. 4. Law and love - Meier, John P. 1942- (New Haven Doubleday, 2009)
Introduction to Volume Four: The Historical Jesus is the Halakic Jesus -- CHAPTER 31. Jesus and the Law - but What Is the Law? -- CHAPTER 32. Jesus’ Teaching on Divorce -- CHAPTER 33. The Prohibition of Oaths -- CHAPTER 34. Jesus and the Sabbath -- CHAPTER 35. Jesus and Purity Laws -- CHAPTER 36. Widening the Focus: The Love Commandments of Jesus -- Conclusion to Volume Four -- Map of Palestine in the Time of Jesus -- Map of the Galilee of Jesus’ Ministry -- Chart of the Family of Herod the Great -- Chart of the Regnal Years of the Roman Principes (Emperors) -- List of Abbreviations -- Scripture and Other Ancient Writings Index -- Author Index -- Subject Index.
Includes bibliographical references and indexes. - Print version record
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jesus Christ -- Historicity; Jesus Christ -- Jewishness; Jesus Christ -- Relations with Jews; Jésus-Christ -- Historicité; Jésus-Christ -- Judai͏̈cité -- Jesus Christ; Jesus Christ -- Historicity; Jesus Christ -- Jewishness; Jesus Christ -- Relations with Jews; Jesus Christ -- Relations with Jews; Jesus Christ -- Jewishness; Jesus Christ -- Historicity; Jesus Christ; Jews -- Palestine -- Middle East -- Palestine; Jews -- Palestine; Jews -- Palestine; Historicity of Jesus Christ; Jewishness of Jesus Christ; Jews; Relations with Jews; Leven van Jezus; Historiciteit; RELIGION ; Christian Theology ; Christology; Middle East ; Palestine; Electronic books; Electronic books